THE EFFECT OF AUDIT QUALITY TO EARNINGS RESPONSE COEFFICIENT WITH INTERVENING VARIABLES AS EARNINGS MANAGERIAL AND PROFIT POLICY - Wahyuni, Ika; Herawaty, Vinola (Universitas Kristen Indonesia, 2018)
The purpose of this study is to determine whether the quality of audit affects earnings response coefficient by using earnings management and debt policy as intervening variables. This research is done by using purposive sampling method. The results of this study can be seen that, KAP size variables do not have a significant influence on debt policy mean a while the variable earnings management (Manlab) has a significant influence on earnings (ERC) in manufacturing companies in Indonesia Stock Exchange. In addition, Debt Policy variables have a significant influence on earnings (ERC), and KAP Size variables with variable debt policy intermediaries have a significant effect on earnings (ERC) on manufacturing companies in Indonesia Stock Exchange. It is expected for the users of information and further researchers, this research can be used as a source of new analysis for variable earning response coefficient.Keywords: Earning Response Coefficient, Audit Quality, Profit Management, Debt Policy